(3QSGdI aj JMbjb CMhGd GdQLGds - (3GdHgHgGfj, GdMGFQj, GdcQeGfTGgj, GdhMjO, CMeO Hf eMeO Ydj Hf eMeO HGbQ, (B1243 (3g`s
(3ChdgG (B:s
... (3Ef GdTjYI JQHi HGdCeGfj heG Od Ydi Pdc eG SfPcQ aj JQLeI jbWjf adGMX ef Pdc Cfge cKjQG eG jSCdhfge Ydjge GdSdGe Yf bGFege UdhGJ Gddg Ydjge aQHeG bGd hGMO efge UdhGJ Gddg Ydjg adGf jYfj GdPj HYO (B...s
(3BNQgG (B:s
... (3heKd GdHRjYjI ; aQbI ef GdNWGHjI jbhdhf HEeGeI HRjY HYO CHj GdNWGH hEe cd eDef jhMi Edjg hCf GdEfSGf EPG HdZ GdceGd dG jbGd dg eGJ Hd QaY Edi GdedchJ (B... (3eYGfjg HcQI hYTjI (B.s
(3JHUQI GdYfhGf (B:s
(3JYdjbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs